Modelo de gestión de control de desempeño, para los equipos de trabajo dentro de la línea de calor de la empresa Indurama S.A. - Serrano Alvarado, Edwin Fernando (2022)
In this investigation, the Hoshin Kanry methodology was used, it was found that waste was reduced by 26% between periods. This was achieved because the members of the work teams participated directly in the problem encountered, this methodology increased the participation of the collaborators from 5% to 40%.